2023
DOI: 10.1038/s41467-023-41681-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards bioresource-based aggregation-induced emission luminogens from lignin β-O-4 motifs as renewable resources

Tenglong Guo,
Yuting Lin,
Deng Pan
et al.

Abstract: One-pot synthesis of heterocyclic aromatics with good optical properties from phenolic β-O-4 lignin segments is of high importance to meet high value added biorefinery demands. However, executing this process remains a huge challenge due to the incompatible reaction conditions of the depolymerization of lignin β-O-4 segments containing γ-OH functionalities and bioresource-based aggregation-induced emission luminogens (BioAIEgens) formation with the desired properties. In this work, benzannulation reactions sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…26 In contrast, aggregation-induced emission (AIE) represents the opposite behavior: luminogens with AIE effect (AIEgens) are non-emissive in the isolated state but can emit bright light in the aggregate state. 27–29 Accordingly, AIEgens are preferable for developing “intelligent” stimuli-responsive optical materials, promoting the continuous exploration of AIE-based materials during the past two decades. 16,30–32…”
Section: Introductionmentioning
confidence: 99%
“…26 In contrast, aggregation-induced emission (AIE) represents the opposite behavior: luminogens with AIE effect (AIEgens) are non-emissive in the isolated state but can emit bright light in the aggregate state. 27–29 Accordingly, AIEgens are preferable for developing “intelligent” stimuli-responsive optical materials, promoting the continuous exploration of AIE-based materials during the past two decades. 16,30–32…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach, our recent work achieved a one-pot transformation of lignin β-O-4 models reacting with 3-alkenylated indole to generate carbazoles catalyzed by vanadium associated with tridentate Schiff-based ligands (Scheme 1b). 47 Nonetheless, this method necessitates the use of organovanadium complexes with intricated ligands and prefunctionalized 3-alkenylated indole derivatives, requiring significant synthetic efforts upfront. Thus, there is a pressing need to explore feasible synthesis routes for multi-substituted carbazole derivatives in an atom-economical and sustainable manner, catalyzed by non-precious metals and commercially available starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…3 Research has shown that the β-O-4 motifs are the most abundant and active linkages in lignin, making them crucial for downstream transformations. 4,5 By incorporating stabilization functions into designed solvent systems, the structure and activity of lignin can be effectively regulated, 6 thereby facilitating the extraction of high yields of lignin monomers or novel lignin streams.…”
Section: Introductionmentioning
confidence: 99%